Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/19443994.2016.1185383
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium recovery using potassium cobalt hexacyanoferrate sorbent

Abstract: A B S T R A C TRubidium (Rb) is a highly valued and economically important metal present in large quantities in many natural and wastewaters. However, its recovery is hampered by its low concentration and extracting agents' limited selectivity. A batch sorption study showed that a potassium cobalt hexacyanoferrate (KCoFC) sorbent had much higher sorption capacities for Rb and caesium (Cs) than for lithium (Li), sodium (Na) and calcium (Ca). Equilibrium sorption data at pH 7 and 24 ± 1˚C for Rb and Cs satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Moreover, at low pH, H + could have competed with Rb for adsorption in the highly acidic solution where the concentration of H + was high, and consequently adsorption capacity declined. Similarly, at high pH the presence of increased concentration of Na (arising from pH adjustment with NaOH) most likely competed with Rb adsorption, thus reducing Rb adsorption capacity [10,11]. The results also indicated that the difference between the zeta potential with and without Rb increased, and the negative surface charge declined in the presence of Rb as pH increased for both adsorbents (Fig.…”
Section: Effect Of Ph On Rb Adsorptionmentioning
confidence: 78%
See 4 more Smart Citations
“…Moreover, at low pH, H + could have competed with Rb for adsorption in the highly acidic solution where the concentration of H + was high, and consequently adsorption capacity declined. Similarly, at high pH the presence of increased concentration of Na (arising from pH adjustment with NaOH) most likely competed with Rb adsorption, thus reducing Rb adsorption capacity [10,11]. The results also indicated that the difference between the zeta potential with and without Rb increased, and the negative surface charge declined in the presence of Rb as pH increased for both adsorbents (Fig.…”
Section: Effect Of Ph On Rb Adsorptionmentioning
confidence: 78%
“…The number of negative charges on the surface of the adsorbent increased with pH. Therefore, the increase in pH elevated the adsorption of positively charged Rb ions by electrostatic adsorption (outersphere complexation) [10,11]. Moreover, at low pH, H + could have competed with Rb for adsorption in the highly acidic solution where the concentration of H + was high, and consequently adsorption capacity declined.…”
Section: Effect Of Ph On Rb Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations